Sociological Analysis of the Cultural Sector - Irina V. Lashuk; Elena V. Taranova (Социологическая наука и социальная практика, 2017)
This article presents theoretical and methodological justification for the sociological analysis of the culture in the modern society. Social studies allow us to analyze the sphere of culture on two different levels: on a symbolic level where the culture is represented in the form of ideas, values, images and exists in the encrypted format, and on a behavioral level where the encrypted values and rules are expressed through real behavioral models. The sociological analysis of culture in the modern society can be performed using the behavioral models of social groups in different fields. These models show us, on the one hand, how values, standards and rules of particular community are being decrypted into real-life, everyday activities, and, on the other hand, how this activities can be encrypted back into the cultural code in the future and how it will affect the following generations. The authors of this article developed a conceptual model and an operational model to analyze social and cultural structure of Belorussian society: 10.6% of the respondents turned out to be “socially and culturally active” (which means that they use existing resources to the highest possible extent); 30.5% turned out to be “mostly active”; 49.5% - “mostly passive”, and 9.3% - “mostly inactive”. This analysis allowed to determine the character of interaction between the social and cultural processes and the economic processes in the context of the development of the Republic of Belarus. It is proven that the respondents with higher social and cultural activity level also show higher economic activity level and strive to improve the quality of their lives.